2015
DOI: 10.1111/jace.13737
|View full text |Cite
|
Sign up to set email alerts
|

Novel BiFeO3–BaTiO3–Ba(Mg1/3Nb2/3)O3 Lead‐Free Relaxor Ferroelectric Ceramics for Energy‐Storage Capacitors

Abstract: A novel lead-free relaxor ferroelectric ceramic of (0.67 -x)BiFeO 3 -0.33BaTiO 3 -xBa(Mg 1/3 Nb 2/3 )O 3 [(0.67 -x)BF-0.33BT-xBMN, x = 0-0.1] was prepared by a solid-state reaction method. A relatively high maximum polarization P max of 38 lC/cm 2 and a low remanent polarization P r of 5.7 lC/cm 2 were attained under 12.5 kV/mm in the x = 0.06 sample, leading to an excellent energy-storage density of W~1.56 J/cm 3 and a moderate energy-storage efficiency of g~75%. Moreover, a good temperature stability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
87
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(95 citation statements)
references
References 19 publications
3
87
1
4
Order By: Relevance
“…6). This should be pinned on the increase of electrical conduction loss and similar phenomena have been reported in polymer and ceramic dielectrics 6,35 . The conduction loss and FE loss of the BFSTO films at various temperatures are decoupled based on the method by Khanchaitit et al 36 , as shown in Supplementary Fig.…”
Section: Resultssupporting
confidence: 72%
“…6). This should be pinned on the increase of electrical conduction loss and similar phenomena have been reported in polymer and ceramic dielectrics 6,35 . The conduction loss and FE loss of the BFSTO films at various temperatures are decoupled based on the method by Khanchaitit et al 36 , as shown in Supplementary Fig.…”
Section: Resultssupporting
confidence: 72%
“…To meet the demands for electrical energy‐storage capacitors in the field of pulsed power applications and the increasing demands of society, dielectric capacitors for high energy‐storage density devices have been widely investigated and have played a vital role, especially in ceramic capacitors . In comparison to batteries and other energy‐storage devices, ceramic capacitors possess a faster charge–discharge rate and superior mechanical and thermal properties .…”
Section: Introductionmentioning
confidence: 99%
“…A slow and slight increase in the P max value can be seen with increasing the temperature, indicating that ergodic and/or nonergodic relaxor states could be transformed into a long-range ferroelectric order 4 . A gradual decrease in P r and the P-E loops become slimmer and slimmer with increasing the temperature, which is attributed to the decrease of content of nonergodic phase 4 . Therefore, the gradual decrease in P r and increase in P max are beneficial to improve energy storage properties over a broad temperature range.…”
Section: Resultsmentioning
confidence: 99%
“…For further evaluating energy storage performance of the (1-x)LLBNTZ-xNBN ceramics, the comparison of W 1 and BDS between (1-x)BBNT-xNBN ceramics and other lead-free ceramics in recently reported results are shown in Fig. 9  1, 4, 10, 14, 16, 22, 23, 37, 40, 6975 . It can be seen that the values of W 1 and BDS for (1-x)LLBNTZ-xNBN ceramics are higher than those of other lead-free ceramics.
Figure 8Calculated energy storage density, energy loss density and energy storage efficiency as a function of electric field for the (1-x)LLBNTZ-xNBN ceramics at room temperature.
Figure 9Comparison of W 1 and BDS between (1-x)LLBNTZ-xNBN ceramics and other lead-free ceramics.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation